ISOLASI DAN AKITIVITAS SPESIFIK ENZIM LIPASE INDIGENOUS BIJI KENARI - Djarkasi, G. S. Suhartati; Raharjo, Sri; Noor, Zuheid (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2017)
In general, plant oil resources has lypase enzyme which can hidrolyze oil to free fatty acids. The free fatty acid formed relatively easier to be oxidazed than that of in the form of triglycerides. The aims of this research are to investigate the specific activity of endogenous lypase enzyme and its optimum temperature. The protein was extracted by ammonium sulphate, dialysed, then fractionated through Sephadex G-100.The research proceeds with measurement activities of endogenous enzyme extracted from canarium kernel. From the research konwn that activities of lypase endogenous from Canarium indicum and Canarium vulgare are similar. It’s known that the more purification factor (PF) attained the higher specific activity (SA) achieved. Crude extract for Canarium indicum with FP=1 gives the SA=0.033 μmol/mg. When the PF is increased become 4.98 with saturation 70 % sodium sulphate, the SA value become 0.16 μmol/mg. Then, purification with sephadex G-100 for column chromatography cause the PF increase to 55.54 and the SA is 1.83 μmol/mg. In addition, for Canarium vulgare the higher PF give the more SA. Crude extract for Canarium vulgare with FP=1 gives the SA=0,033 μmol/mg. When the PF increase becomes 4.57 with saturation 70 % sodium sulphate, the SA value is 0.17 μmol/mg. Then, purification with sephadex G-100 for column chromatography, the PF increase to 51.13 and the SA is 1.94 μmol/mg. The optimum temperature of endogenous lipase from Canarium indicum is similar to lipase endogenous from Canarium vulgare, i.e 40°C. The free fatty acid content of Canarium indicum and Canarium vulgare kernel are 0.19±0.06% and 0.20±0.04%, respectively. After drying, free fatty acid content of Canarium indicum and Canarium vulgare kernel increase to 0.30±0.04% and 0.37±0.06%, respectively. The increase of free fatty acid has positive correlation with lipase activities.